Terminally Differentiated CD4+ T Cells Promote Myocardial Inflammaging - Delgobo, Murilo; Heinrichs, Margarete; Hapke, Nils; Ashour, DiyaaElDin; Appel, Marc; Srivastava, Mugdha; Heckel, Tobias; Spyridopoulos, Ioakim; Hofmann, Ulrich; Frantz, Stefan; Ramos, Gustavo Campos (Frontiers in Immunology, 2021)
The cardiovascular and immune systems undergo profound and intertwined alterations with aging. Recent studies have reported that an accumulation of memory and terminally differentiated T cells in elderly subjects can fuel myocardial aging and boost the progression of heart diseases. Nevertheless, it remains unclear whether the immunological senescence profile is sufficient to cause age-related cardiac deterioration or merely acts as an amplifier of previous tissue-intrinsic damage. Herein, we sought to decompose the causality in this cardio-immune crosstalk by studying young mice harboring a senescent-like expanded CD4+ T cell compartment. Thus, immunodeficient NSG-DR1 mice expressing HLA-DRB1*01:01 were transplanted with human CD4+ T cells purified from matching donors that rapidly engrafted and expanded in the recipients without causing xenograft reactions. In the donor subjects, the CD4+ T cell compartment was primarily composed of naïve cells defined as CCR7+CD45RO-. However, when transplanted into young lymphocyte-deficient mice, CD4+ T cells underwent homeostatic expansion, upregulated expression of PD-1 receptor and strongly shifted towards effector/memory (CCR7- CD45RO+) and terminally-differentiated phenotypes (CCR7-CD45RO-), as typically seen in elderly. Differentiated CD4+ T cells also infiltrated the myocardium of recipient mice at comparable levels to what is observed during physiological aging. In addition, young mice harboring an expanded CD4+ T cell compartment showed increased numbers of infiltrating monocytes, macrophages and dendritic cells in the heart. Bulk mRNA sequencing analyses further confirmed that expanding T-cells promote myocardial inflammaging, marked by a distinct age-related transcriptomic signature. Altogether, these data indicate that exaggerated CD4+ T-cell expansion and differentiation, a hallmark of the aging immune system, is sufficient to promote myocardial alterations compatible with inflammaging in juvenile healthy mice.